Caudal analgesia versus abdominal wall blocks for pediatric genitourinary surgery: systematic review and meta-analysis. Issue 11 (14th September 2020) - Desai, Neel; Chan, Edmund; El-Boghdadly, Kariem; Albrecht, Eric
Abstract : Background: Caudal block is a well-established technique for providing perioperative analgesia in pediatric genitourinary surgery, but abdominal wall blocks such as ilioinguinal–iliohypogastric (II-IH) and transversus abdominis plane (TAP) block are increasingly being used. Methods: Our protocol for this meta-analysis was registered on PROSPERO (CRD42020163497). Central, CINAHL, Embase, Global Health, LILACS, MEDLINE, Scopus and Web of Science were searched from inception to 11 December 2019 for randomized controlled trials that included pediatric patients having genitourinary surgery with II-IH or TAP block as the intervention and caudal analgesia as the comparator. For continuous and dichotomous outcomes, respectively, we calculated the mean difference using the inverse-variance method and the risk ratio with the Mantel-Haenzel method. Results: In all, 23 trials with 1399 patients were included. II-IH and TAP block were similar to caudal analgesia in the coprimary outcomes of the postoperative pain score at 0–2 hours (high-quality evidence) and the need for in-hospital rescue analgesia (moderate-quality evidence consequent to downgrading by publication bias). No subgroup differences in regard to the type of abdominal wall block or the method of block localization were demonstrated for these primary outcomes. Relative to caudal analgesia, II-IH and TAP block reduced the incidence of postoperative motor blockade and the time to micturition. Conclusions: This meta-analysis was limited by unclear risk of selection and performance biases and significant heterogeneity. In summary, II-IH and TAP block are a non-invasive and reasonable alternative to caudal analgesia in pediatric genitourinary surgery.